Small cell neuroendocrine carcinoma of the cervix: diagnostic challenges and emerging molecular insights - Charbel, Alphonse; Akiki, Gaëlle; Diwan, Sarah-Slim; Leung, Shuk On Annie; Kommoss, Felix; Tessier-Cloutier, Basile (The journal of pathology, 2025)
Small cell neuroendocrine carcinoma of the cervix (SCNECC) is a rare and highly aggressive malignancy with poor prognosis that predominantly affects premenopausal women. Histopathological evaluation is central to diagnosis and clinical management; however, distinguishing SCNECC from other ‘small blue round cell’ malignancies often requires a multimodal approach that integrates morphology, immunohistochemistry, and advanced molecular testing. In the absence of specific and sensitive biomarkers, SCNECC largely remains a diagnosis of exclusion, underscoring the need for comprehensive diagnostic algorithms. A study by Pan, Yan, Yuan et al employed whole transcriptome profiling and identified three molecular subgroups within SCNECC. Importantly, one subgroup displayed an inflamed phenotype, characterized by high expression of MHC-II complex and IFN-α/β-related genes, suggesting potential susceptibility to immunotherapy, a finding that mirrors observations in small cell lung cancer. These findings highlight the biological heterogeneity of SCNECC and reinforce the importance of integrating molecular data to refine diagnostic accuracy and guide therapeutic decision-making. This commentary emphasizes the pressing need for comprehensive diagnostics and further research to advance treatment strategies for this rare and challenging malignancy. © 2025 The Pathological Society of Great Britain and Ireland.
Gesehen am 25.02.2026